2012
DOI: 10.1128/mcb.06305-11
|View full text |Cite
|
Sign up to set email alerts
|

The General Transcription Factor TAF7 Is Essential for Embryonic Development but Not Essential for the Survival or Differentiation of Mature T Cells

Abstract: e TAF7, a component of the TFIID complex that nucleates the assembly of transcription preinitiation complexes, also independently interacts with and regulates the enzymatic activities of other transcription factors, including P-TEFb, TFIIH, and CIITA, ensuring an orderly progression in transcription initiation. Since not all TAFs are required in terminally differentiated cells, we examined the essentiality of TAF7 in cells at different developmental stages in vivo. Germ line disruption of the TAF7 gene is embr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
58
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 39 publications
(45 reference statements)
8
58
0
1
Order By: Relevance
“…Preliminary findings indicate that this is the case: In a variety of cells, there is a molar excess is embryonic lethal between 4.5 and 5.5 d post coitus, the time at which the embryo implants and undergoes marked cellular expansion. 26 Taken together, these findings suggest that all cells have a requirement for TAF7 to proliferate.…”
Section: Taf7 Regulates the Major Rnap II Ctd Kinasesmentioning
confidence: 78%
See 1 more Smart Citation
“…Preliminary findings indicate that this is the case: In a variety of cells, there is a molar excess is embryonic lethal between 4.5 and 5.5 d post coitus, the time at which the embryo implants and undergoes marked cellular expansion. 26 Taken together, these findings suggest that all cells have a requirement for TAF7 to proliferate.…”
Section: Taf7 Regulates the Major Rnap II Ctd Kinasesmentioning
confidence: 78%
“…TAF7-/-MEFs are blocked throughout cell cycle. 26 Furthermore, overexpression of TAF7 in MEFs also does not cause a specific cell cycle arrest (unpublished data). Thus, although TAF7 interacts with TAF1 and BRD4, mutation or deletion of either causes an arrest in cell cycle at the G1/S interface, TAF7 deletion does not have a similar effect.…”
Section: Taf7 Regulates the Major Rnap II Ctd Kinasesmentioning
confidence: 89%
“…Because lck-cre + mice differ from WT mice, care should also be taken when interpreting results using only an lck-cre + control. Intriguingly, some investigators reported no differences between lck-cre + or lck-cre 2 mice, whereas others did (17,19,21,(29)(30)(31)(32)(33)(35)(36)(37) (Fig. 6).…”
Section: Discussionmentioning
confidence: 91%
“…TAF expression is lost in some differentiated cell types, including hepatocytes, myotubes, and Drosophila wings (13)(14)(15). Although the canonical TAFs are essential for proliferating cells, they are not essential for survival or even proliferation-independent differentiation of postmitotic cells (16,17). Consistent with this finding, depletion or inactivation of some of the TAFs causes cell-cycle arrest (18)(19)(20)(21).…”
mentioning
confidence: 74%